Foto Selfie sebagai Daya Tarik Minat Khusus di Anjungan Tukad Melangit (ATM) Kabupaten Bangli - I Wayan Wiwin (UHN IGB Sugriwa Denpasar, 2017)
A special interest tourism has become the current tourism trend, where special interest tourism is a kind of alternative tourism to avoid the development of mass tourism which tend to have negative impact so far. The special interest tourism that became a new phenomenon in the world of tourism became one of the demands for the providers of tourist services. The motivation of tourists in finding something new and having a quality tourist experience leads to increasea demand for special interest tourists. Especially for the providers of tourism services in Bali are required to provide a new innovations, interesting and different from usual. One of the special interest tourism potential that is currently being uploaded in social media is selfie photo tour at Tukad Melangit Pavilion (ATM) located in Antugan Hamlet, Jehem Village, Tembuku Subdistrict, Bangli Regency. But the potential of tourism has not been explored to the maximum so it is necessary to make the development program development efforts to increase the number of tourist visits